New mechanisms of optical harmonic generation in semiconductors - Kaminski, Benjamin (Technische Universität Dortmund, 2010)
In this work two novel mechanisms of optical harmonic generation in semiconductors are presented and analysed on the basis of symmetry restrictions and the specific electronic structures. The first mechanism is observed in the hexagonal semiconductor ZnO. Since its valence and conduction band have different parity, electric-dipole second harmonic generation (SHG) processes are symmetry forbidden for light incidence perpendicular to the c-plane. Nevertheless, the nonlinear spectroscopy of ZnO reveals narrow peaks in the spectral range from 3.4 to 3.5 eV, which are induced by an external magnetic field. Microscopic model calculations establish the magneto-optical Stark effect as the main mechanism for the detected SHG involving 2S and 2P exciton states. The effect results from the center-of-mass motion of excitons in the magnetic field. This motion leads to a perturbation equivalent of an electric field and causes an admixture of states with different parities. The second mechanism is found in europium chalcogenides magnetic semiconductors. EuTe and EuSe are investigated by the spectroscopy of second harmonic generation and third harmonic generation (THG) in the vicinity of the optical band gap formed by transitions involving the 4f and 5d electronic orbitals of the magnetic Eu2+ ions. In these materials with a centrosymmetric crystal lattice, the electric-dipole SHG process is symmetry forbidden so that no signal is observed in zero magnetic field. Signal appears, however, in applied magnetic fields with the SHG intensity being proportional to the square of magnetization. The magnetic field and temperature dependencies of the induced SHG allow us to introduce a novel type of nonlinear optical susceptibility determined by the magnetic-dipole contribution in combination with a spontaneous or induced magnetization. The experimental results can be described qualitatively by a phenomenological model based on a symmetry analysis and are in good quantitative agreement with microscopic model calculations accounting for details of the electronic energy and spin structure. Contrary to the SHG, electric dipole THG contributions are allowed for centrosymmetric materials. Consequently, a crystallographic third harmonic generation signal, showing different resonances, is found in europium chalcogenides over wide spectral ranges. In an external magnetic field a resonant induced magnetic contribution appears additively. Enhanced by a double resonance of the electric dipole THG process, the detected signal is of higher magnitude than the spin induced SHG signal.
Keywords: Second harmonic generation; SHG; Third harmonic generation; THG; Europium chalcogenides; Zinc oxide; ZnO; EuTe; EuSe; Spin induced SHG; Magneto optical Stark effect; Exciton; Nonlinear spectroscopy; Centrosymmetric material; Centrosymmetry; 530